Health Care Access and Equity Among Migrants: A Literature Review - Nur, Zilvi Fuadiyah; Suryadarma, Antonius Yansen; Mengistu, Assaye Girma; Pangestuti, Ayu; Ariza, Nahya Rahmatul; Mahmudiono, Trias (UNUSA Press, 2024)
Background: Health inequality often occurs among disadvantaged population groups, including migrants. Currently, the migrant population does not always receive adequate health services. In addition, the health care system is not optimized for migrants, especially in terms of language, access, genomic data and the expertise of medical personnel. The health condition of these migrants is a global problem that needs attention if countries want to meet the Sustainable Development Goals (SDGs) targets by 2030. Purpose: to map the latest existing research on the topic of migrant health, both qualitative and quantitative. Methods: narrative literature review and literature search were carried out using an electronic database with the automatic selection feature used in the electronic database according to the specified inclusion criteria. Results: Obtained an overview of inequality in [1] access to health services for migrants in general, [2] utilization of health services and health-seeking behavior, [3] health literacy, [4] health services related to the COVID-19 pandemic, and [5] maternal and child health services. All authors agree on this division of groups. Conclusion: Migrants who do not have documents or are illegal, skin color (black migrants) who migrate to western countries, languages ​​that are not the same, and do not understand their own health conditions due to lack of health education due to language barriers, these factors are obstacles for migrants to achieve equality in countries where migrants have migrated.